EFEKTIFITAS BERMAIN PLAY DOUGH UNTUK MENINGKATKAN MOTORIK HALUS DALAM MEMEGANG ALAT TULIS BAGI ANAK TUNAGRAHITA RINGAN - Lusiana - (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstrak: The study exposed the problem found by researcher in the SLB N 1 Padang, a mental retardation child who had probelms on his fine motor in holding the stationery. This research aimed to prove whwther playing play Dough is effective to improve fine motor in holding stationery for mild mental retardation child at V SLB Land class 1 Padang This research used experimental approach in the form of single subject research(SSR), used the design of the A-B-A and the data analysis techniques used visual analysis charts. The conclusion was plasying Play Dough was effective to improve fine motor for mild mental retardation child. Key Word: Playing Play Dough; Fine Motor; Mental Retardation Child.